Characterisation Of Cellulose Nanocrystals From Oil Palm Fronds For Carboxymethyl Cellulose Bio-Nanocomposites - Nordin, Noor Afeefah (2018)
Cellulose nanocrystals (CNC) were produced from oil palm fronds (OPF) to produce carboxymethyl cellulose (CMC)-cellulose nanocrystals bio-nanocomposite. A fundamental study on top, middle and bottom parts of raw oil palm fronds was conducted and based on the scanning electron microscope (SEM) images, it showed that the bottom part of OPF had greater percentage of vascular bundles compared to middle and top parts. It was further supported by chemical analysis that showed bottom part of OPF had the highest α-cellulose content. The top, middle and bottom parts of OPF were further utilised to produce CNC by applying chemo-mechanical treatment.